Introduction to computer graphics : using Java 2D and 3D - Klawonn, Frank (Undergraduate topics in computer science, 2012)
This book provides an introduction to the basic concepts of computer graphics. It couples the technical background and theory immediately with practical examples and applications. The reader can follow up the theory and then see the theory at work in example programs